Reparations for Nazi victims in postwar Europe - Ludi, Regula (Cambridge : Cambridge University Press, 2012)
"Reparations of Nazi Victims in Postwar Europe traces reparations back to their origins in the final years of the Second World War, when victims of Nazi persecution for the first time articulated demands for indemnification en masse. Simultaneous appearance of claims in New York, London, Paris and Tel Aviv exemplified the birth of a new standard in political morality. Across Europe, the demand for compensation to individuals who suffered severe harm gained momentum. Despite vast differences in their experiences of mass victimisation, post-war societies developed similar patterns in addressing victims' claims. Regula Ludi chronicles the history of reparations from a comparative and trans-national perspective. This book explores the significance of reparations as a means to provide victims with a language to express their unspeakable suffering in a politically meaningful way"--
Introduction -- War's end and blueprints for a new world order -- France : the dialectics of suffering and sacrifice -- Germany : Hitler's many victims and the survivors of Nazi persecution -- Switzerland : neutralizing the past -- Conclusion : talking about victimization : a European model.
Includes bibliographical references (pages 242-264) and index.
Keywords: Europa; 1939 - 1945; Claims; War reparations; World War, 1939-1945 -- Reparations; World War, 1939-1945 -- Claims; World War, 1939-1945 -- Europe; Reparations for historical injustices -- Europe; War victims -- Legal status, laws, etc; HISTORY -- Europe -- General; Reparations for historical injustices; War victims -- Legal status, laws, etc; Europe; Claims